2019
DOI: 10.3928/23258160-20190129-01
|View full text |Cite
|
Sign up to set email alerts
|

Current Management of Macular Hole

Abstract: In this issue's Practical Retina column, Sumit Randhir Singh, MD, and Raja Narayanan, MD, MBA, from the LV Prasad Eye Institute in Hyderabad, India, discuss the current therapeutic options for repairing macular holes (MHs). We are all aware that there is great discussion and wide variability in thinking among our colleagues regarding approaches to close a MH. Common controversies include when and if internal limiting membrane peeling is necessary, as well as what to do with it after it is peeled (fully or part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
2
3
0
Order By: Relevance
“…The mean age in our data is 61.9 ± 17.31 (11-93) years which is almost similar to reported in the literature [ 13 , 15 ] indicating no significant age difference in this pathology in the Asian population. The total mean operating time reported in our data is slightly longer compared with the 25-gauge system [ 15 ], a finding reported before as well [ 4 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The mean age in our data is 61.9 ± 17.31 (11-93) years which is almost similar to reported in the literature [ 13 , 15 ] indicating no significant age difference in this pathology in the Asian population. The total mean operating time reported in our data is slightly longer compared with the 25-gauge system [ 15 ], a finding reported before as well [ 4 ].…”
Section: Discussionsupporting
confidence: 90%
“…None of the eyes developed sclerotomy site leakage, post-operative early or late hypotony, and endophthalmitis, a major concern previously [ 5 - 7 ]. None of the eyes in our study developed RRD as reported previously [ 13 , 29 ] so we recommend meticulous complete vitreous shaving with scleral depression. Mean BCVA has significantly improved in our study as reported previously as well [ 15 , 1 ].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In ad- Practical Retina dition to providing a scaffold, the ILM tissue may contain Müller cell fragments, which has been postulated to induce gliosis, and in turn may enhance MH closure. 9,14,15 The inverted ILM flap technique for large MHs, which was first described by Michalewska et al, utilizes a wide ILM with care to detach the peripheral macular ILM while keeping the ILM attached around the MH. 14 The detached ILM is then inverted and placed into the MH, followed by fluid-air-exchange.…”
Section: Mh Scaffoldsmentioning
confidence: 99%
“…Being relatively new technique, inverted ILM flap technique, which was first proposed and described by Michalewska et al, became very popular among vitreoretinal surgeons due to its efficacy and favorable postoperative results [1]. Up until now, the variety of modifications of the technique with the use of ILM flap was proposed [2]. The differences between these technique modifications shall be without any doubt appreciated and well distinguished.…”
mentioning
confidence: 99%